2023
DOI: 10.3389/fimmu.2023.1078958
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-engineering of HMC-1.2 cells renders a human mast cell line with a single D816V-KIT mutation: An improved preclinical model for research on mastocytosis

Abstract: The HMC-1.2 human mast cell (huMC) line is often employed in the study of attributes of neoplastic huMCs as found in patients with mastocytosis and their sensitivity to interventional drugs in vitro and in vivo. HMC-1.2 cells express constitutively active KIT, an essential growth factor receptor for huMC survival and function, due to the presence of two oncogenic mutations (D816V and V560G). However, systemic mastocytosis is commonly associated with a single D816V-KIT mutation. The functional consequences of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…While HMC‐1.1 cells contain one mutation in KIT (V560G), HMC‐1.2 cells express two KIT mutations (V560G and D816V). As a result, constitutive, oncogenic KIT signalling (pJAK2, pAKT, pERK) is enhanced in HMC‐1.2 cells compared to HMC‐1.1 cells (Figure 4b ) (Bandara et al., 2023 ). In the presence of KIT inhibitors, the activation of these downstream signalling proteins was equally blocked (Figure 4c ).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…While HMC‐1.1 cells contain one mutation in KIT (V560G), HMC‐1.2 cells express two KIT mutations (V560G and D816V). As a result, constitutive, oncogenic KIT signalling (pJAK2, pAKT, pERK) is enhanced in HMC‐1.2 cells compared to HMC‐1.1 cells (Figure 4b ) (Bandara et al., 2023 ). In the presence of KIT inhibitors, the activation of these downstream signalling proteins was equally blocked (Figure 4c ).…”
Section: Resultsmentioning
confidence: 95%
“…A comparative analysis of transcriptomic data obtained from HMC‐1.1 and HMC‐1.2 cells (Bandara et al., 2023 ) revealed that endocytic processes were significantly upregulated in HMC‐1.2 cells (Figure S4 ). Since KIT is highly phosphorylated in HMC‐1.2 cells (Figure 1a ) and RTKs are endocytosed after activation, we sought to examine whether internalisation of KIT was required for the stimulated exosome‐like sEV release.…”
Section: Resultsmentioning
confidence: 99%